Spectroscopic study on luminescent mechanochromic transition metal complexes - Ko, Chi-Chiu (2020)
Luminescent mechanochromic materials that are capable of undergoing reversible mechanical-induced transformations between two forms with different luminescent behaviors have received great attention. To date, a number of different types of luminescent mechanochromic compounds including simple organic compounds, polymers and transition metal complexes have been reported [1-2]. The luminescent mechanochromism of many of these solids is derived from reversible switching between the crystalline states and the amorphous state through which the intermolecular interactions, such as π-π, H-bonding, dipole-dipole, metal-metal and metal-ligand interactions, and thus the energy of the electronic states and the luminescence are varied [1-2].